APPLICATION OF POINT OF SALES WEB STORE DVD / VCD USING PHP CONTENT MANAGEMENT SYSTEM (JOOMLA) - Cherry Mariz Wibowo; Ire Puspa Wardhani, Ir, MMSi Ire Puspa Wardhani, Ir, MMSi (Jurnal Sistem Informasi, 2008)
Content Management System (Conten Management System) known as the CMS is a web-based application that has such a system to provide convenience to the users as well as its organizer. In accordance with CMS's name itself, a website that implements this system is oriented towards content. It was not a significant constraint to management or public relations a company, institution, or organization to update its website. With access rights and authority of each, every part of the company, institution, or organization can contribute to this website without difficult procedures.